Analisis Lembar Kerja Siswa Praktikum Biologi SMA Pada Materi Uji Kandungan Zat Makanan: (Analysis of Student Worksheets of Biology Practicum in High School on Subject Matter Test Food Content) - Frima Harsawati Frima; Sri Anggraeni; Bambang Supriatno (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
This study aims to provide an overview of student worksheet on practicum used in schools. the research method used was qualitative descriptive method and the sample were 5 student worksheets selected using a purposive sampling. The research instrument used is conceptual analysis and practical analysis using instrument form analysis of laboratory activities and analysis of knowledge construction based on the scoring table of Diagram Vee adapted from Novak & Gowin (1984). The results showed that most of the student worksheet test of food content did not reach the demands of Basic Competence. This can be seen from the conceptual analysis. The cognitive level that arises in practicums is only to remember. Then for the practical analysis of the Test Food Content worksheet that is analyzed is not yet relevant to the demands of basic competencies. While the knowledge construction analysis using the Novak & Gowin instrument shows that most procedural steps can be done but are less relevant to the purpose of the practicum, do not bring up the object / event in accordance with the focus question, practicum questions in student worksheets are largely unanswered based on the results of laboratory activities, not lead to the formation of knowledge claims and less help students in linking the knowledge they have with the facts observed. Abstrak. Penelitian ini bertujuan memberikan gambaran lembar kerja siswa pada praktikum yang digunakan di sekolah. Metode penelitian yang digunakan adalah metode penelitian deskriptif kualitatif dengan sampel penelitian berjumlah 5 LKS yang dipilih dengan menggunakan teknik purposive sampling. Instrumen penelitian yang digunakan yaitu analisis konseptual dan analisis praktikal menggunakan instrumen form analisis kegiatan laboratorium dan analisis konstruksi pengetahuan berdasarkan tabel penskoran Diagram Vee yang diadaptasi dari Novak & Gowin (1984).Â Hasil penelitian menunjukkan bahwa sebagian besar LKS uji kandungan zat makanan tidak mencapai tuntutan Kompetensi Dasar. Hal tersebut dapat dilihat dari analisis konseptual Tingkat kognitif yang muncul pada praktikum hanya mengingat saja. Kemudian untuk analisis praktikal LKS Uji Makanan yang dianalisis belum relevan dengan tuntutan kompetensi dasar. Sedangkan analisis konstruksi pengetahuan menggunakan instrumen Novak & Gowin menunjukkan Sebagian besar langkah prosedural dapat dikerjakan namun kurang relevan dengan tujuan praktikum, tidak memunculkan object/event yang sesuai dengan pertanyaan fokus, Pertanyaan praktikum pada LKS sebagian besar tidak dapat terjawab berdasarkan data hasil kegiatan laboratorium, tidak mengarahkan pada pembentukkan knowledge claim serta kurang membantu siswa dalam mengaitkan pengetahuan yang telah dimilikinya dengan fakta yang diamati.